"Providing a complete episode of care": A survey of registered nurse and registered midwife prescribing behaviours and practices. Issue 1 (6th November 2019) - Casey, Mary; Rohde, Daniela; Higgins, Agnes; Buckley, Tom; Cashin, Andrew; Fong, Jacqueline; Hughes, Mary; McHugh, Aine
Abstract: Aims and objectives: To describe the prescribing behaviours and practices of registered nurse and midwife prescribers and to explore experiences of enablers and barriers to prescribing practices. Background: The extension of prescriptive authority to nurses and midwives internationally has created new opportunities for them to expand their scope of practice and is of significant benefit to effective and efficient health service provision. Design: Cross‐sectional national survey of registered nurse and midwife prescribers. Methods: Data were collected through an online survey between April–July 2018. A total of 84 nurse and midwife prescribers participated. The STROBE checklist was applied as the reporting guideline for this study. Results: Respondents estimated that two‐fifths of their consultations involved an episode of prescribing. Nurse and midwife prescribers engaged in similar prescribing behaviours spanning the range of activities from initiating new medications to ceasing medicines. The most frequently selected criterion for prescribing was clinical effectiveness. Prescribing was viewed as essential to respondents' clinical practice, allowing them to provide a complete episode of care and leading to a reduction in medication errors and reduced delays and waiting times for patients. Enablers of prescribing included knowledge, experience, education and access to continuous professional development, as well as support from colleagues and organisations. Conclusion: Little is known about the prescribing behaviours and practices of registered nurse and midwife prescribers. While prescribing authority enables nurse and midwife practitioners to deliver holistic care, there remain significant barriers and challenges including increased workloads, lack of continuous professional development, lack of support and overly restrictive rules and policies governing prescribing. Relevance to clinical practice: Addressing the barriers identified in this study could enable more nurse and midwife prescribers to work to their full scope of practice, enabling populations to fully capitalise on the contributions of registered nurse and midwife prescribing services.